Oral sensory dysfunction following radiotherapy. (11th April 2017) - Bearelly, Shethal; Wang, Steven J.; Cheung, Steven W.
Abstract : Objectives/Hypothesis: To assess differences in oral tactile sensation between subjects who have undergone radiation therapy (XRT) compared to healthy controls. Study Design: Cross‐sectional cohort comparison. Methods: Thirty‐four subjects with a history of XRT were compared with 23 healthy controls. There was no difference in age ( P = .23), but there were slightly more males in the XRT cohort ( P = .03). The mean (standard deviation) time after XRT completion was 3.84 (4.84) years. Fifty‐six percent of the XRT cohort received chemotherapy. Using our previously validated methodology to measure oral tactile sensory threshold quantitatively with Cheung‐Bearelly monofilaments, sensory thresholds of four subsites (anterior tongue, buccal mucosa, posterior tongue, soft palate) were compared for the two cohorts. Results: Site‐by‐site comparisons showed higher forces were required for stimulus detection at all four subsites among subjects in the XRT cohort compared to healthy controls. Mean force in grams for XRT versus control cohorts were: anterior tongue, 0.39 (1.0) versus 0.02 (0.01); buccal mucosa, 0.42 (0.95) versus 0.06 (0.05); posterior tongue, 0.76 (1.46) versus 0.10 (0.07); and soft palate, 0.86 (1.47) versus 0.08 (0.05) ( P < .001 for all comparisons). Combining all four subsites into a single metric to assess an overall level of oral tactile dysfunction, the XRT cohort had reduced sensation by 18.7 dB ( P < .001). Conclusions: After radiation therapy, the oral cavity and oropharynx exhibit global tactile sensory dysfunction, manifested by increased tactile forces required for stimulus detection. The magnitude of sensory impairment is 18.7 dB. Level of Evidence: 3b. Laryngoscope, 127:2282–2286, 2017